Controlling embryonic stem cell proliferation and pluripotency: the role of PI3K- and GSK-3-dependent signalling. (22nd March 2011) - Welham, Melanie J.; Kingham, Emmajayne; Sanchez-Ripoll, Yolanda; Kumpfmueller, Benjamin; Storm, Michael; Bone, Heather
Abstract : ESCs (embryonic stem cells) are derived from the inner cell mass of pre-implantation embryos and are pluripotent, meaning they can differentiate into all of the cells that make up the adult organism. This property of pluripotency makes ESCs attractive as a model system for studying early development and for the generation of specific cell types for use in regenerative medicine and drug screening. In order to harness their potential, the molecular mechanisms regulating ESC pluripotency, proliferation and differentiation (i.e. cell fate) need to be understood so that pluripotency can be maintained during expansion, while differentiation to specific lineages can be induced accurately when required. The present review focuses on the potential roles that PI3K (phosphoinositide 3-kinase) and GSK-3 (glycogen synthase kinase 3)-dependent signalling play in the co-ordination and integration of mouse ESC pluripotency and proliferation and contrast this with our understanding of their functions in human ESCs.